SPLENIC ARTERY SYNDROME AFTER LIVER TRANSPLANTATION – PREDICTIVE FACTORS: EXPERIENCE OF A CENTER - L., Domingues (2021)
Splenic artery syndrome (SAS) is described as a decrease in hepatic artery (HA) flow associated with increased flow in the splenic artery (SA). The present study aim was to identify predictive factors of SAS. A retrospective study was conducted in 70 patients, undergoing liver transplantation (LT) between 03/2010 until 08/2016. The case group (n=27) corresponded to the patients who developed SAS and the control group (n=43) to the patients who didn’t develop. The donor, recipient and graft variables were collected. Significant differences were observed in relation to spleen volume 1137,4±512,9) cm3 vs 523,9±258,1cm3, spleen volume/ liver volume ratio 0,9±0,3 vs 0,4±0,2, difference in caliber between SA and HA 2,1±1,6mm vs 0,8±1,5mm, and the ratio between spleen volume and body mass index (BMI) of the recipient 47,9±24,5 vs 18,9±8,8 between the case and control group respectively. In case group the mean difference between pre-embolization and post-embolization resistive index (RI) was 0.2±0.1, which demonstrates a significant improvement after embolization of the SA (p<0.001, CI: 95% 0.11-0.25). In logistic regression, the retained variable was only the spleen volume (p<0.05), and the cut-off point was 1023.9 cm3. It’s possible to conclude that spleen volume is a risk factor for SAS. It’s also important to note that significant differences between groups were evident in relation to the ratio spleen volume/liver volume and difference in caliber between SA and HA in the pre-LT. In this sense, it’s relevant in future studies to develop a prospective methodological design in order to analyze the predictive value of these variables.